UPAYA MENINGKATKAN HASIL BELAJAR PESERTA DIDIK MENGGUNAKAN MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) PADA PELAJARAN IPA - Mursilah, Mursilah (Elementary School Teacher and Education (PGSD), Faculty of Teacher Training and Education, 2020)
The purpose of this research was to improve student learning outcomes using the contextual teaching and learning model (CTL), in natural science lessons on the sub-theme of plants as a source of life, design research of Classroom Action Research (CAR), two cycles and four stages each; plans, actions, observations and reflections. The research subject were class VI elementary school number 51/IX Setiris Muaro Jambi, consisting of 22 students. Data collection techniques used observation and formative tests, Data analysis used simple tabulation calculations, the success criteria are ?73 individually and 100% classical, the results showed that, learning success score 18% increased to 64% in the first cycle and increased again to 100% in the second cycle, with the highest score of 84, the lowest score of 73 and an average score of 79.71, teacher observation by 70% increased to 88%, student observation by 65% increased to 85%. Therefore, it can be concluded that the CTL learning model can improve student learning outcomes in natural science on the sub-theme of plants as a source of life in class VI students of elementary school number 51 / IX Setiris Muaro Jambi district.